(untitled) (Proceedings of the YSU C: Geological and Geographical Sciences, 2001)
Initiating cryogenic ehodynamic system is one of the most progressive geomorphologic factors of relief formatting in landscape of Armenia and Artsakh highland zone (altitudes over 2 000 m). The article surveys climatic preconditions for developing of different cryogenic processes sub-types, their essence, nature and differences as well as microforms and sediments evolving alongside with them. Nivation is responsible for slips, Karrooids, scratched-up cones whereas cross- solifluxion causes slow movement of alluvial shingles and hillocks erecting. Polygonal gettings, stone rings, medallions originate from the ground freezing and thawing in periods of seasonal frosts. Cryogen processes carry negative impact on economic activities of man. This fact calls for detailed studies, wide range works for map drawing and drafting of nature protection program.